A study on fuzzy cognitive maps using fuzzy inference system - Appasamy Saraswathi; Seyyed Edalatpanah; Sanaz Hami Hassan Kiyadeh (Big Data and Computing Visions)
Fuzzy Mathematics theory has been studied extensively in this study. Most early interest in fuzzy set theory pertained to representing uncertainty in human cognitive processes. Fuzziness can be found in many areas of daily life, such as engineering, business, medical and related health sciences, and the natural sciences. It is particularly frequent, however, in all areas in which human judgment, evaluation and decisions are important. However, in many real-life cases, the decision data of human judgments with preferences are often vague, so the traditional ways of using crisp values are inadequate. Due to a lack of information, the future state of the real system might not be known completely. Fuzzy mathematical modelling represents a real-world problem in a mathematical form to find solutions to the problem that correspond closely to how humans perceive it. Also, fuzzy modelling increases the validity of ill-structured systems by offering a deeper understanding of the complexities of decision parameters. In this paper, we analyze the problem of the transgender using FCMs and Combined Fuzzy Cognitive Maps (CFCM). This paper is divided into five sections. Section one introduces the basic introduction of transgender and the previous research of Fuzzy Cognitive Maps (FCM) and Combined FCM. Section two introduces FCM and combined FCM and the basic operations. Section three shows the basic definitions of FCM and Combined CFCM. The fourth section provides methods to analyze transgender problems using combined FCM. The final section gives the conclusions and some suggestions based on our study.